2005
DOI: 10.1093/gerona/60.5.627
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Characteristics of Forward and Backward Gait at Preferred and Accelerated Walking Speed

Abstract: Elderly persons demonstrate difficulties in walking backward, with stride length particularly affected. These difficulties must be considered when using backward ambulation for rehabilitation of elderly persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
89
3
11

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(119 citation statements)
references
References 31 publications
16
89
3
11
Order By: Relevance
“…The studies reported here define negative geotaxis in Drosophila as a climbing behavior that decreases with age due to reduced speed of locomotion. Since age-related reductions in walking speed are also observed in humans (Oberg et al 1993;Bohannon 1997;Kozakai et al 2000;McGibbon and Krebs 2001;Samson et al 2001;Laufer 2005), our studies highlight the conserved effects of age on locomotor function in humans and flies. It will be intriguing to further investigate genetic mechanisms that influence senescence of negative geotaxis in Drosophila and explore whether these mechanisms play a role in locomotor senescence in other species.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The studies reported here define negative geotaxis in Drosophila as a climbing behavior that decreases with age due to reduced speed of locomotion. Since age-related reductions in walking speed are also observed in humans (Oberg et al 1993;Bohannon 1997;Kozakai et al 2000;McGibbon and Krebs 2001;Samson et al 2001;Laufer 2005), our studies highlight the conserved effects of age on locomotor function in humans and flies. It will be intriguing to further investigate genetic mechanisms that influence senescence of negative geotaxis in Drosophila and explore whether these mechanisms play a role in locomotor senescence in other species.…”
Section: Discussionsupporting
confidence: 67%
“…One of the hallmarks of locomotor senescence in elderly individuals is a decrease in walking speed (Oberg et al 1993;Bohannon 1997;Kozakai et al 2000;McGibbon and Krebs 2001;Samson et al 2001;Laufer 2005). Importantly, age-related reduction in walking speed in the elderly population is correlated with walking impairment (Brach et al 2007) and is associated with increased risk of several co-morbidities and death (Hardy et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be done through the quantification of the same parameters used in assessment scales, like the time to complete the test in TUGT (see [7]), quantification of mobility or gait parameters associated with fall risk (cf. [55], [56], [57], [58] and [59]) or using machine learning techniques, with the ground truth provided by clinically accepted scales (cf. [47], [32], [48], [6] and as suggested in [50]).…”
Section: Recent Studies On Fall Risk Predictionmentioning
confidence: 99%
“…Several measures can be quantified during gait from accelerometer signal, which include gait velocity, cadence, step length, stride length, step time, stride time, swing time and double support time [56,58,67], using the informations from peak detection algorithms [78].…”
Section: Gait Parametersmentioning
confidence: 99%